Kuliner Sebagai Identitas Budaya: Perspektif Komunikasi Lintas Budaya - Sri Utami (CoverAge: Journal of Strategic Communication, 2018)
The word "culinary" is defined as something related to, or connected with, cooking. Cooking transforms food from nature to culture. Food sustains life. At the same time, it symbolizes social life and cultural identity for various groups of people throughout the world. Indeed, every nation has its own culinary which has been gradually accepted and becomes a taken-for-granted culinary ideology. Culinary is also an indicator of how these develop and alter over time and space. With this in mind, this paper will explore how culinary represents cultural identity in cross-cultural communication in various ways. Within these relationships, culinary is recognized as a source of power. Culinary is both a relevant source of signification and an effective form of communication of distinctive culture, with strong national character and diversity of features. Understanding culinary of the differences and its profound cultural connotation, explore their cultural heritage, and promote further exchanges of culturre.